Initial survey on fresh fruit and vegetable preferences of Neumayer Station crew members: Input to crop selection and psychological benefits of space-based plant production systems - Mauerer, Mareike; Schubert, Daniel; Zabel, Paul; Bamsey, Matthew; Kohlberg, Eberhard; Mengedoht, Dirk (Open Agriculture, 2016)
The inclusion of higher plants in bio-regenerative life support systems has been suggested to contribute to a nutritious menu, increase food acceptability and provide psychological benefits to the crew. In 2017, the EDEN ISS project will deploy a greenhouse module to the Neumayer Station III in Antarctica. This system will be used to advance bio-regenerative life support system technologies and operations. An initial survey was conducted to improve crop selection for the EDEN ISS greenhouse module by further investigating the aspects of food acceptability and psychological benefits of crop cultivation. Former members of the overwintering crews of the three Neumayer stations were asked about their fresh food and vegetable preferences and about further aspects concerning Antarctic plant production. Results confirm the benefits of growing higher plants in isolated and confined environments and offer insight on the importance of crop selection aspects like taste, texture, pungency and colour.